RETRACTED: Disulfiram Chelated With Copper Inhibits the Growth of Gastric Cancer Cells by Modulating Stress Response and Wnt/β-catenin Signaling - Wang, Ling; Chai, Xiaoke; Wan, Run; Zhang, Hong; Zhou, Cong; Xiang, Lin; Paul, Maswikiti Ewetse; Li, Yumin (Frontiers in Oncology, 2020)
Abstract. Disulfiram (DSF) is a well-known drug for alcohol abuse. In recent decades, DSF has been demonstrated to exhibit anti-tumor activity; DSF chelated with copper shows enhanced anti-tumor effect. Our goal was to explore the effect of DSF/Cu complex on the growth and metastasis of gastric cancer (GC) in vitro and in vivo. DSF/Cu complex suppressed the proliferation, migration, and invasion of MKN45 GC cells. Furthermore, DSF/Cu treatment reduced the tumor volume in GC mouse models with a tumor suppression rate of 48.24%. Additionally, DSF/Cu induced apoptosis in vitro in MKN45 GC cells in a dose- and time-dependent manner as well as in vivo in the xenograft tumor mouse model. Furthermore, DSF/Cu induced autophagy and autophagic flux in MKN45 cells and increased the expression of autophagy related Beclin-1 and LC3 proteins in vivo. Additionally, DSF/Cu suppressed aerobic glycolysis and oxidative phosphorylation by reducing oxygen consumption rate and extracellular acidification rate, respectively, in MKN45 cells. Treatment with DSF/Cu induced oxidative stress and DNA damage response by elevating the reactive oxygen species levels; increasing the expression of P53, P21, and gamma-H2AX proteins; and inhibiting Wnt/β-catenin signaling in vitro and in vivo. Thus, DSF/Cu suppressed the growth and metastasis of GC cells via modulating the stress response and Wnt/β-catenin signaling. Hence, DSF may be used as a potential therapeutic agent for the treatment of GC.